2009
DOI: 10.1002/adem.200800403
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Behavior of Radiopaque NiTiPt Hypotube for Biomedical Applications

Abstract: Nitinol (NiTi) has become one of the most important implant materials in biomedical applications such as endovascular stents, embolic protection filters, and endodontic files. However, NiTi stents sometimes do not provide satisfactory visibility under fluoroscopy during angioplasty. A new ternary alloy, radiopaque nitinol (NiTiPt), exhibits much better radiopacity than NiTi and has great potential for future biomedical applications. This paper presents the first characterization of anisotropic stress-strain be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
(6 reference statements)
2
10
0
Order By: Relevance
“…Among the radiopaque elements, so far only the addition of Pt has been investigated in some useful form, e.g. wire and hypotube, but without describing any details on the materials processing or any quantitative value of the improvement in radiopacity [1,4,5]. Mehrabi et al [23] reported a high hardness of W-alloyed NiTi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the radiopaque elements, so far only the addition of Pt has been investigated in some useful form, e.g. wire and hypotube, but without describing any details on the materials processing or any quantitative value of the improvement in radiopacity [1,4,5]. Mehrabi et al [23] reported a high hardness of W-alloyed NiTi.…”
Section: Resultsmentioning
confidence: 99%
“…stainless steel and Co-Cr alloys) used in minimally invasive surgery are inherently less visible due to their weak X-ray absorption ability (radiopacity) [1,3]. Dense and high atomic number elements such as platinum (Pt) have been added to NiTi [1,[4][5][6] and stainless steel [7] to enhance radiopacity.…”
Section: Introductionmentioning
confidence: 99%
“…The nitinol material behavior for the ABAQUS UMAT subroutine inputs was obtained from Pham et al [ 46 ]. The material ultimate strain and fatigue endurance limits used in the fatigue life analysis were 10% and 1%, respectively [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, conventional NiTi SMAs exhibit also high electrical resistance, low mechanical damping and low visibility under fluoroscopy1617, which severely limit their usefulness in applications. Ag has good visibility under fluoroscopy and is one of the best electrically conductive materials possessing high electrical conductivity.…”
mentioning
confidence: 99%
“…NiTi shape-memory alloys (SMAs), due to their excellent shape-memory effect, superelasticity and biocompatibility, are used for many products, such as cellular phone antennae, spectacle frames, medical guidewires and stents 13 14 15 . Unfortunately, conventional NiTi SMAs exhibit also high electrical resistance, low mechanical damping and low visibility under fluoroscopy 16 17 , which severely limit their usefulness in applications. Ag has good visibility under fluoroscopy and is one of the best electrically conductive materials possessing high electrical conductivity.…”
mentioning
confidence: 99%